TEACHING OF ETERNAL RETURN: A VISION BASED TEACHING PHILOSOPHY OF FRIEDRICH NIETZSCHE - Toledo Gutiérrez, Carlos (2014)
Peruvian teachers’ situation in state schools is defined by the magisterial nihilism that is mining the spirit and sense of the educational activity protagonists. Meanwhile, in pedagogy, do we have great and new questions? Great and relevant goals and purposes? Everything has already been said in pedagogy? Bioeducation, that is to say, education at the service of a life concept, a concept based in a saying yes to life, yes to our educational reality, to practice the Never-ending return, to build an attitude of educator, of persons former. Training in curriculum, lead by Education Ministry, is qualified as compulsive, the “new faith”. Are we before a slow process of extinction or decomposition of Peruvian teachers and state educational institutions, under the details of the magisterial nihilism illness?